Prognostic relevance of left atrial function and stiffness in heart failure with preserved ejection fraction patients with and without diabetes mellitus - Zhu, Shuangshuang; Lin, Yixia; Zhang, Yanting; Wang, Guohua; Qian, Mingzhu; Gao, Lang; Ji, Mengmeng; Xie, Mingxing; Li, Yuman; Zhang, Li (Frontiers in Cardiovascular Medicine, 2022)
Background Although the left atrium (LA) plays a key role in the pathophysiology and disease progression of heart failure with preserved ejection fraction (HFpEF), the impact of type 2 diabetes mellitus (T2DM) on LA function and stiffness in HFpEF patients remains unclear. Furthermore, the prognostic value of different phases of LA function and stiffness is less well-established in HFpEF patients. Methods This study prospectively enrolled 164 HFpEF patients who were in sinus rhythm at the time of echocardiography, including 61 (37%) HFpEF patients with T2DM. LA reservoir, conduit, and pump function were assessed using two-dimensional volume indices and speckle tracking echocardiography. The LA stiffness was calculated as the ratio of early mitral inflow velocity-to-early annular tissue velocity (E/e’) and LA reservoir function. The primary end point was a combined outcome of heart failure hospitalization or death. Results Left atrium reservoir function [measured by peak LA strain (LAS-peak)] and LA pump function (measured by LAS-active) remained significantly lower in the HFpEF patients with T2DM compared with those without T2DM, even after adjustment for potential confounders. In addition, the LA stiffness of HFpEF patients with T2DM was higher than those without T2DM. After a median follow-up of 13.7 months, 46 patients (28.1%) reached the composite end point. LAS-peak (hazard ratios: 0.88; 95% confidence interval: 0.81–0.95; P = 0.001) was significantly associated with the risk of heart failure hospitalization or death after adjusting for demographic and clinical characteristics, LV global longitudinal strain, E/e’, and LA volume index. In contrast, other LA function and stiffness parameters did not independently predict the risk of adverse events. Kaplan-Meier analysis showed that HFpEF patients with T2DM and low LAS-peak (<27.2%) had a significantly increased risk of heart failure-related hospitalization or death (log-rank P < 0.001). Conclusion Left atrium reservoir and pump function are impaired, whereas LA stiffness is increased in HFpEF patients with T2DM compared with those without T2DM. LAS-peak is a powerful predictor of adverse clinical outcomes and may be crucial for risk stratification in HFpEF patients with and without T2DM.